Long-term validation of the GRACE and PRECISE-DAPT scores in patients with non-ST elevation acute coronary syndrome. (14th October 2021) - Garcia-Rodeja Arias, F; Alvarez Alvarez, B; Gonzalez Ferrero, T; Abou Jokh Casas, C; Otero Garcia, O; Martinon Martinez, J; Jimenez Ramos, V; Garcia Acuna, J M; Rigueiro Veloso, P; Agra Bermejo, R M; Iglesias Alvarez, D; Cacho Antonio, C; et al.
Abstract: Introduction and objectives: There is insufficient data regarding risk scores validation in patients with diabetes mellitus and non-ST elevation acute coronary syndrome (NSTEACS). We performed a diabetes mellitus-specific analysis of cardiovascular outcomes after NSTEACS using a large contemporary cohort of patients from two tertiary hospitals. Methods: This work is a retrospective analysis from a prospective registry, that included 7415 consecutive NSTEACS patients from two Spanish Universitary Hospitals between the years 2003 and 2017. We tested the predictive power of the GRACE and PRECISE DAPT score, calculating the area under the ROC curve among with and without diabetes mellitus patients. Results: Among the study participants, 2124 patients (28.0%) were diabetic. The median follow up was 54, 3 months (IQR 24.7–80.0 months). Diabetic patients were more women (30.5% vs 25.7%) and older (70.0±10.8 vs 65.3±13.2 years old); they had higher GRACE (146±36 vs 137±36), PRECISE DAPT (15±7 vs 18±9) and CRUSADE (17±14 vs 30±18) at admission. Early invasive coronary angiography (≤24 hours after admission) was performed more frequently in non-diabetic. We tested the predictive power of the GRACE and PRECISE DAPT risk scores among diabetic and non-diabetic. PRECISE DAPT risk score showed a good predictive power for all-cause mortality, cardiovascular mortality and MACE in diabetic admitted with NSTEACS, without differences compared to non diabetic. Conclusions: PRECISE DAPT risk score has an appropriate predictive power in diabetic patients admitted with NSTEACS compared to non diabetic NSTEACS. However, GRACE would be predictive worse in non diabetic during long term follow up in a large contemporary registry. Funding Acknowledgement: Type of funding sources: None.